Determinants of Islamic Banking Profitability in Indonesia - A'la, Sabila Hikmatul; Darmansyah, Asep (Journal of Business and Management, 2021)
Any economic growth and stability mostly depend on its banking sector. However, the ROA of conventional banks in Indonesia always higher than Islamic banks in the previous 5 years period. This research focuses on finding the internal-bank factors that may affect the profitability of Islamic banks in Indonesia. Internal-bank factors as independent variables that tested in this research are bank size (SIZE), Capital Adequacy Ratio (CAR), Liquidity of Assets (LIQ), Operational Efficiency (BOPO), Gearing Ratio (GR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR). Return on Asset (ROA) used as dependent variable which represent profitability of banks. The data samples have passed the classical assumption test and continued with multiple linear regression. The result shows that partially SIZE and BOPO give a negative significant effect on ROA. CAR, LIQ, GR gives a positive significant influence on ROA. NPF and FDR have no effect on profitability of Islamic banks in Indonesia. The simultaneously significant effect is given by SIZE, CAR, LIQ, BOPO, GR, NPF, and FDR on the ROA of Islamic banks in Indonesia. Keywords: Bank size, Capital Adequacy Ratio, Liquidity of Assets, Operational Efficiency, Gearing Ratio, Non-Performing Financing, Financing to Deposit Ratio, Return on Asset.